Advances in small molecule two-photon fluorescent trackers for lipid droplets in live sample imaging - Lee, Dong Joon; Kim, Eun Seo; Lee, Hyo Won; Kim, Hwan Myung (Frontiers in Chemistry, 2022)
Two-photon fluorescent trackers for monitoring of lipid droplet (LD) would be highly effective for illustrating the critical roles of LDs in live cells/tissues. Although a number of one-photon fluorescent trackers for labeling LDs have been developed, they are restricted in live sample imaging due to the photodamage, shallow imaging depth, and auto-fluorescence. Recently, some of two-photon fluorescent trackers for LDs are developed to overcome those limitations. In this mini-review article, the advances in two-photon fluorescent trackers for monitoring of LDs are summarized. We summarize the chemical structures, two-photon properties, live sample imaging, and biomedical application of the most recent representative two-photon fluorescent trackers for LDs. In addition, the current challenges and future research trends for the two-photon fluorescent trackers of LDs are discussed as well.